Factors influencing the choice between transcatheter and surgical treatment of severe aortic stenosis in patients younger than 80 years: Results from the OBSERVANT study. Issue 6 (18th August 2019) - Tarantini, Giuseppe; Nai Fovino, Luca; D'Errigo, Paola; Rosato, Stefano; Barbanti, Marco; Tamburino, Corrado; Ranucci, Marco; Santoro, Gennaro; Badoni, Gabriella; Seccareccia, Fulvia; ,
Abstract: Objectives: We aimed to analyze the baseline features and clinical outcomes of patients younger than 80 years undergoing transfemoral transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (SAVR) enrolled in the OBservational Study of Effectiveness of SAVR‐TAVR procedures for severe Aortic steNosis Treatment (OBSERVANT) real‐world study, focusing on variables guiding Heart Team decision toward TAVI. Background: Patients treated with TAVI, independently of surgical risk score, are mostly older than 80 years. Methods: OBSERVANT is a multicenter, observational, prospective cohort study that enrolled patients with symptomatic severe aortic stenosis (AS) who underwent SAVR or TAVI from December 2010 to June 2012 in 93 Italian participating hospitals. For this analysis, baseline characteristics, therapeutic approach and outcomes up to 5 years of follow‐up of 4, 801 patients under 80 years of age were collected. Patients were stratified by age classes (<65, 65–74, and 75–79 years). Results: Patients <80 years of age with severe symptomatic AS undergoing TAVI ( n = 483) had significantly higher Logistic EuroSCORE (10.84% vs. 5.22%, p  < .001) and prevalence of comorbidities compared to subjects undergoing SAVR ( n = 4, 318). The decision to perform TAVI over SAVR was driven by anatomical factors, mainly previous cardiac surgery (odds ratio [OR] 24.73, confidence interval [CI] 12.71–48.10, p  < .001) and the presence of porcelain aorta (OR 17.44, CI 6.67–45.55, p  < .001), and clinical factors, mainly moderate–severe frailty score (OR 5.49, CI 3.33–9.07, p  < .001), oxygen dependency (OR 7.42, CI 2.75–20.04, p  < .001) and need for dialytic treatment (OR 5.24, CI 1.54–17.80, p  < .008). Among patients undergoing TAVI, those under 65 years had the highest baseline risk profile (despite a low Logistic EuroSCORE) and the highest 5‐year mortality compared to those 65–74 and 75–79‐year‐old (65.22% vs. 48.54% vs. 55.24%, log‐rank p = .061). Conclusion: Among patients under 80 years of age with symptomatic severe AS, only 10% underwent TAVI. These patients were at higher baseline risk compared to those undergoing SAVR. The decision to perform TAVI was driven by the presence of both anatomical and clinical factors beyond surgical risk scores. Patients under 65 years of age, despite the low Logistic EuroSCORE, had the highest preoperative risk profile and carried the worse outcome.